Associations between psychological stress and smoking, drinking, obesity, and high blood pressure in an upper middle‐income country in the African region. (6th June 2017) - Chamik, Tanja; Viswanathan, Bharathi; Gedeon, Jude; Bovet, Pascal
Abstract: The direction and magnitude of the associations between cardiovascular risk factors (CVRFs) and psychological stress continue to be debated, and no data are available from surveys in the African region. In this study, we examine the associations between CVRFs and psychological stress in the Seychelles, a rapidly developing small island state in the African region. A survey was conducted in 1, 240 adults aged 25–64 years representative of the Seychelles. Participants were asked to rank psychological stress that they had experienced during the past 12 months in four domains: work, social life, financial situation, and environment around home. CVRFs (high blood pressure, tobacco use, alcohol drinking, and obesity) were assessed using standard procedures. Psychological stress was associated with age, sex, and socioeconomic status. Overall, there were only few consistent associations between psychological stress and CVRFs, adjusting for age, sex, and socioeconomic status. Social stress was associated with smoking, drinking, and obesity, and there were marginal associations between stress at work and drinking, and between financial stress, and smoking and drinking. Psychological stress was not associated with high blood pressure. These findings suggest that psychological stress should be considered in cardiovascular disease prevention and control strategies.